General and LGBTQ-specific factors associated with mental health and suicide risk among LGBTQ students. (26th November 2019) - Gnan, Georgina H.; Rahman, Qazi; Ussher, Greg; Baker, Dan; West, Elizabeth; Rimes, Katharine A.
ABSTRACT: This study investigated general and LGBTQ-specific factors associated with having a current mental health problem, use of mental health services, suicide risk and self-harm in 1948 LGBTQ university students (ages 16-25) who took part in the Youth Chances community study in the UK. In multivariate logistic regression, factors associated with all four outcomes were female gender, sexual abuse, other abuse or violence, and being transgender. Further factors that were significantly associated with one or more of the outcomes included: being bisexual; thinking they were LGBTQ under the age of 10; coming out as LGBTQ under the age of 16; not feeling accepted where they live; having no out staff at university and experiencing LGBTQ-related crime. In addition to general risk factors, negative experiences relating to being LGBTQ may be associated with the increased risk for mental health problems, suicide risk and self-harm in LGBTQ students.